Seeing Yourself Through the Learner's Eyes: Incorporating Smart Glasses Into Objective Structured Teaching Exercises for Faculty Development. Issue 1 (14th June 2023) - Reed, Trent; Wagner, Sarah; Ozark, Gregory; Chaidez, Cynthia; Boyle, Mary; Gruener, Gregory
Abstract : Introduction: Although physicians gain clinical knowledge in their specialty, it does not mean they receive adequate instruction to teach and provide feedback. Using smart glasses (SG) to provide educators with a first-person learner perspective has not been explored in faculty development such as Objective Structured Teaching Exercises (OSTEs). Methods: Integrated within a 6-session continuing medical education–bearing certificate course, this descriptive study involved one session where participants provided feedback to a standardized student in an OSTE. Participants were recorded by mounted wall cameras (MWCs) and SG. They received verbal feedback on their performance based on a self-designed assessment tool. Participants reviewed the recorded content and identified areas for improvement, completed a survey about their experience with SG, and wrote a narrative reflection. Results: Seventeen physicians at the assistant professor level participated in the session; data were analyzed on the 14 who had both MWC and SG recordings and who also completed the survey and reflection. All were comfortable with the standardized student wearing SG and indicated it did not affect communication. Eighty-five percent of the participants felt the SG provided additional feedback not available with the MWC, with majority noting additional feedback was related to eye contact, body language, voice inflection, and tone. Eighty-six percent see value in using SG for faculty development, and 79% felt that periodically using SG in their teaching would improve quality. Conclusion: Use of SG during an OSTE on giving feedback was a nondistracting and positive experience. SG provided affective feedback otherwise not perceived from a standard MWC.